(untitled) (Journal of Hama University, 2022)
This study aimed to develop a spatial Decision Support System (DSS) to evaluate Logistics Efficiency of land freight and its developmental reflections on regional scale and create their evaluation map through develop conceptual framework as first step on two stages: 1 - based on "Logistics Planning" Concept it was specified areas of Logistics efficiency after that it was specified Secondary indicators of it, 2- based on "Regional Logistics Planning" Concept it was selected the secondary indicators which have a developmental effects and was separated it as an separated mean indicator "developmental reflections of Logistics Efficiency", the second step was using Fuzzy Analytical Hierarchy Process (FAHP) where was developed the questionnaire which is included in this method by conducting it with experts stakeholders who giving freight service, they are experts in goods freight office in study area, As finally step the developed methodology was applied on the region of developmental axis Tartous-Homs-AlFarquls which was detected in the National Framework for Regional Planning in governorates Hama, Homs and Tartous after was collected its data for year 2018. The development of conceptual framework provided a full vision about the secondary indicators which should be used in assessment the logistics efficiency, as well as the mean indicator "developmental reflections of Logistics Efficiency" which was developed would help policy makers in discussing mutual dramatic changes which will be happen between logistics efficiency and its developmental reflections, whereas the developed spatial decision-making tools in Geographic Information System (GIS) platform helped to analyze highly complex spatial data and showed advantages , potentials, disadvantages and needs of each area that what would make it a fundamental stage in programming the Regional Plan according to real stakeholders.